HUBUNGAN KELENTURAN PERGELANGAN TANGAN DENGAN KEMAMPUAN PUKULAN SMASH FOREHAND PADA PERMAINAN TENIS MEJA - Ilham; La Sawali; Badaruddin (Journal Olympic (Physical Education, Health and Sport), 2022)
This study aims to determine the relationship between wrist flexibility and forehand smash ability in table tennis games for male students of class VIII SMP Negeri 1 Tongkuno. This research method includes descriptive research using a quantitative correlational design using a correlational design. The sample in this study was obtained by purposive sampling technique, namely the sample was selected with consideration of male gender and who could hit the forehand smash. The population in this study were male students of Class VIII SMP Negeri 1 Tongkuno totaling 131 people consisting of 91 girls and 40 boys, taking a sample of 40 people. The formulation of the problem in this study is whether there is a relationship between wrist flexibility and forehand smash ability in table tennis games for VIII male students of SMP Negeri 1 Tongkuno?. The instrument used to measure the wrist flexibility test is the goniometer test, while the instrument used to measure the forehand smash ability test is by hitting the forehand smash 10 times per student. The data of this study were analyzed using SPSS version 26 with a significant level of 0.05 where the value of rxy = 0.646 at a significant 0.00 <0.05 with a coefficient of determination of 41.7%, while 58.3% was influenced by other physical condition factors that were not included in this study. It can be concluded that the better the wrist flexibility, the better the forehand smash ability in the table tennis game for the eighth grade male students of SMP Negeri 1 Tongkuno.